2018
DOI: 10.2147/tcrm.s181381
|View full text |Cite
|
Sign up to set email alerts
|

Complex calculation or quick glance? Mean platelet volume – new predictive marker for pulmonary embolism

Abstract: BackgroundWells and Geneva scores are widely used in the assessment of pretest probability of pulmonary embolism (PE).ObjectiveThe objective of this study was to examine the hypothesis that mean platelet volume (MPV) may better predict PE than the clinical prediction rules.MethodsA study was performed among patients with PE. Baseline characteristics and complete blood counts including MPV were prospectively recorded upon admission. To assess clinical probability in patients with PE risk, we used Wells and Gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…28 Our study demonstrated the utility of complete blood count data to supplement sPESI, but it is important to explore additional parameters. Other studies found elevated MPV useful in diagnosis of acute PE 24 as well as predictive of all-cause mortality. 14,23 Increased MPV has been associated with platelet activation and adhesion which occur in acute PE.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…28 Our study demonstrated the utility of complete blood count data to supplement sPESI, but it is important to explore additional parameters. Other studies found elevated MPV useful in diagnosis of acute PE 24 as well as predictive of all-cause mortality. 14,23 Increased MPV has been associated with platelet activation and adhesion which occur in acute PE.…”
Section: Discussionmentioning
confidence: 97%
“…PE pathophysiology reflects dysregulation of coagulation, inflammatory and hematologic processes. 17 , 18 , 22 There is growing evidence of laboratory parameters predictive of all-cause mortality, including MPV, 14 , 23 , 24 blood cellular ratios, 12 , 13 , 23 , 25 RDW, 15 and anemia, 11 few studies have incorporated multiple parameters into existing risk prediction models. It is necessary to further explore using blood cellular indices to predict all-cause mortality to improve current PE treatment algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…25 Larger platelets contain more granules and prothrombotic substances, have greater thrombogenic potential, and are more prone to aggregate and consumption. 26,27 The newly produced and released young platelets in the bone marrow have also a larger volume and reactivity. 28 Moreover, inflammation activates platelets, increasing their volume.…”
Section: Discussionmentioning
confidence: 99%
“…MPV, an easy to obtain, a cost-effective, and reliable parameter is regarded as a convenient biomarker that can be calculated from routine blood tests [ 5 , 10 ]. There were different cut-off values of MPV with variable diagnostic power for different clinical situations [ 8 , 11 14 ].…”
Section: Highlight Key Pointsmentioning
confidence: 99%
“…Serial measurements of MPV indicating its trend might be useful in predicting risk of PE in patients with the first episode of acute proximal DVT [ 13 ]. Although no solid evidence has been consistently reported for the diagnostic or prognostic value of MPV in thromboembolic conditions, it can be speculated that it might be a useful tool for the initial estimation of thromboembolism risk [ 10 ]. In a recent meta-analysis, results that showed an association between higher values of MPV and both the occurrence and related mortality in PE suggested that it could be used as a predictor that was cheap and easy to test in clinical practice.…”
Section: Highlight Key Pointsmentioning
confidence: 99%